Structural Equation Modeling Algorithm and Its Application in Business Analytics - Sorooshian, Shahryar (IGI Global, 2017)
Structural Equation Modeling (SEM) is a statistical-based multivariate modeling methods, Application of SEM is similar but more powerful than regression analysis; and number of scientists using SEM in their research is rupidly inereasing. This review article algorithmically discussesthe SEM methodology. SEM strategies, SEM steps and SEM stages are introduced in this article; validity tests are presented os well. Novelty of this article is in modified steps of SEM application in modeling strategies, also in its developed practical comprehensive SEM application flowchart This article is a roadmap for business advisors and those scholars trying to compute SEM for their decision making, complex modeling and data analysis programming,